2022
DOI: 10.1002/rcs.2365
|View full text |Cite
|
Sign up to set email alerts
|

Application of deterministic networking for reducing network delay in urological telesurgery: A retrospective study

Abstract: Background: Deterministic Networking (DetNet) is a new technology that can effectively control network delay and may promote the revolution of telemedicine.This study verified the feasibility and advantage of deterministic networking in telesurgery.Methods: All telesurgeries employed the 'MicroHand S' surgical robot system. The network mode adopted fixed-line and 5G wireless networks, while the network configuration scheme adopted DetNet and general networking. The telesurgery data of three patients using DetN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Yang et al in 2022 performed an ultra-remote radical cystectomy (network communication distance of nearly 3000 km) on patient diagnosed with T2N0M0 stage bladder cancer through a 5G network with a mean round-trip transporting delay of 104 ms and a 0% data PLR [31]. In 2022, Zhang reported that their team performed Unilateral nephrectomy in 5G wireless network and deterministic networking (DetNet) mode with an average network delay of 27 ms and a 0% data PLR [32]. Under the regulation of ONTMS, electrophysiological signals and highdefinition video during telesurgery can be transported smoothly, with an average round-trip transporting delay of about 76 ms and a PLR of 0.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yang et al in 2022 performed an ultra-remote radical cystectomy (network communication distance of nearly 3000 km) on patient diagnosed with T2N0M0 stage bladder cancer through a 5G network with a mean round-trip transporting delay of 104 ms and a 0% data PLR [31]. In 2022, Zhang reported that their team performed Unilateral nephrectomy in 5G wireless network and deterministic networking (DetNet) mode with an average network delay of 27 ms and a 0% data PLR [32]. Under the regulation of ONTMS, electrophysiological signals and highdefinition video during telesurgery can be transported smoothly, with an average round-trip transporting delay of about 76 ms and a PLR of 0.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the telesurgery system presented in the literature [ 30 , 31 ] uses a universal 5G network, which has a greater network transmission delay than that of this system, even though it is being used by the network operator trying its best to guarantee the quality of service during the telesurgery. Furthermore, the telesurgery system introduced in the literature [ 32 , 33 ] adopts DetNet and VPNe networks, but DetNet is usually more costly to build and maintain; the VPNe network depends on the public Internet stability, which may affect the availability of the VPNe network if the Internet is unstable or fails. The delay is within the 200 ms delay range recommended in the literature [ 34 , 35 ] for remote surgical operations and even shorter than the visual evoked potential time (P100 wave with an average peak latency of 97.73 ± 3.55 ms) [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…They apply UDP and the Real-Time Messaging Protocol (RTMP), tune the encoder, and further apply data compression. In another representative work, Zhang et al [ 141 ] utilise DetNet for telesurgery, integrating time-sensitive networking (TSN), software-defined network (SDN), and other technical features for a more deterministic network with low latency and jitter. Qiong et al [ 142 ] propose deep Q-learning to predict the optimal minimum contention window (MCW) for improved vehicular communication and age fairness.…”
Section: Latency Mitigation Strategiesmentioning
confidence: 99%